Grain refinement method for manufacturing pure aluminum through laser powder bed melting additive
By mixing titanium dioxide particle powder with pure aluminum powder in laser powder bed melt additive manufacturing technology, grain refinement is achieved, solving the problem of poor mechanical properties of pure aluminum and aluminum alloys in 3D printing process, and improving the mechanical properties of the materials.
Patent Information
- Application Number
- CN202411916957.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
AI Technical Summary
In 3D printing based on high-energy velocity flow, pure aluminum and aluminum alloys usually grow in the form of columnar crystals, which are affected by large residual stresses, resulting in poor mechanical properties.
Grain refinement is achieved by uniformly mixing commercial titanium dioxide particles with pure aluminum powder and using laser powder bed melt additive manufacturing technology. Titanium dioxide reacts chemically with aluminum during melting, and titanium is distributed as a solute in the aluminum matrix, hindering grain growth.
The grain refinement of pure aluminum is achieved, which can withstand more thermal stress, reduce or eliminate columnar crystals, reduce anisotropy, and improve mechanical properties.
Smart Images

Figure CN119839308A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of additive manufacturing, and in particular to a grain refinement method for additively manufacturing pure aluminum using laser powder bed melting. Background Art
[0002] Aluminum is the most abundant metal element in the earth's crust, with advantages such as low density, high thermal conductivity and low cost. Aluminum alloys with aluminum as the main element can be used as lightweight and high-strength structural materials. They are often used to manufacture various lightweight and high-load parts and structural parts. They are widely used in civil and military fields such as aerospace, automobiles, ships, and electronic products. Traditional processing methods, such as casting and forging, usually require the use of molds, and it is difficult to manufacture and form complex structures. Additive manufacturing has gained more and more attention due to its free-forming characteristics. However, in the 3D printing (additive manufacturing) process based on high-energy flow, the thermal gradient is large and the solidification rate is very fast. Pure aluminum and aluminum alloys usually grow in the form of columnar crystals and are affected by large residual stress. Therefore, it is expected that in the process of additive manufacturing of pure aluminum and aluminum alloys, a grain refinement method for laser powder bed melting additive manufacturing of pure aluminum can achieve grain refinement, withstand more thermal stress, reduce or completely eliminate columnar crystals, reduce anisotropy and improve mechanical properties. Summary of the invention
[0003] In order to overcome the shortcomings of the prior art, based on the technical defects of laser 3D printing technology, obtaining pure aluminum and other aluminum alloys easily produces large columnar crystals and poor mechanical properties, one of the purposes of the present invention is to provide a grain refinement method for laser powder bed melting additive manufacturing of pure aluminum.
[0004] The second object of the present invention is to provide an aluminum product produced by the above-mentioned laser powder bed melting additive manufacturing method for grain refinement of pure aluminum.
[0005] One of the purposes of the present invention is achieved by the following technical solution: A method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing comprises the following steps: S1: uniformly mix pure aluminum powder and titanium oxide powder in a mass ratio of (98-99.5):(0.5-2) to obtain a mixed powder; S2: The mixed powder is placed in a laser powder bed melting additive manufacturing forming device, and grain refinement is performed on it with a laser power of 200-400 W, a scanning rate of 200-2000 mm / s, a scanning spacing of 0.08-0.12 mm, and an interlayer thickness of 0.3 mm.
[0006] That is, the present invention can achieve grain refinement and more thermal stress-bearing effects of pure aluminum during the printing process by mixing in commercial titanium oxide particle powder. During the rapid cooling process of printing, titanium oxide and pure aluminum are both melted and chemically reacted. After the reaction, titanium remains in the aluminum matrix in the form of solute atoms and hinders the growth of grains during the solidification process. Therefore, the structure of pure aluminum is directly refined in the absence of other heterogeneous nucleation particles. This method is easy to operate and provides a new idea for achieving grain refinement of high-performance aluminum alloys.
[0007] Among them, titanium oxide is a purple inorganic compound with a melting point of about 2130°C, which is commonly used in the field of semiconductor materials. Titanium oxide is introduced into pure aluminum during the laser powder bed melting additive manufacturing process and reacts chemically with aluminum in an ultra-high temperature molten pool. Under the strong reducing conditions of aluminum, titanium decomposes from titanium oxide and, under the action of the Marangoni flow, is evenly dispersed in the molten pool as a solute. Since titanium has the highest shape restriction factor value of all elements in aluminum alloys (about 220), it hinders the growth of grains during solidification to achieve the purpose of refining the structure.
[0008] Furthermore, in step S1, a pre-processing step is also included: The pure aluminum powder was placed in a vacuum drying oven for drying.
[0009] Since pure aluminum usually contains impurities and it is difficult to achieve 100% purity, such as aluminum oxide, silicon, iron, copper, tin, etc., pure aluminum includes a series of aluminum alloys such as oxide, silicon, iron, copper, tin, etc., also known as the pure aluminum series, which has a high aluminum content, usually above 99%.
[0010] Furthermore, in step S1, the particle size of the pure aluminum powder is 15-53 μm, wherein the pure aluminum is commercial pure aluminum powder.
[0011] Furthermore, the particle size of the nano titanium oxide powder is 0.00006~0.2 of the particle size of the pure aluminum powder. By selecting the optimal particle size ratio with the pure aluminum powder, the cracking of 3D printed pure aluminum is reduced to achieve grain refinement of the alloy. Preferably, the particle size of the nano titanium oxide powder is 1~1000nm. Since the larger the particle size of the material, the easier it is to agglomerate and the relatively high cost, more preferably, the particle size of the nano titanium oxide powder is 20~900nm, and most preferably, the particle size of the nano titanium oxide powder is 20~80nm. Among them, the nano titanium oxide powder is commercial nano titanium oxide powder.
[0012] Furthermore, in step S1, the specific method for uniformly mixing the powders is as follows: Put pure aluminum powder and titanium oxide powder in a mass ratio of (98~99.5):(0.5~2) into a three-dimensional swinging mechanical powder mixer, and quickly flip, invert and shake for 2~3 hours at a frequency of not less than 20Hz to mix them evenly.
[0013] Among materials with different particle sizes, the above-mentioned mixing method can better distribute the materials evenly, so as to improve the grain refinement of the materials during subsequent laser printing.
[0014] Furthermore, in step S1, a post-processing step is also included: The mixed powder was placed in a vacuum drying oven for drying.
[0015] Furthermore, in step S2, the laser power is 300-380 W, the scanning rate is 1000-1800 mm / s, and the scanning spacing is 0.1 mm, so as to obtain a high-strength aluminum alloy with extremely high density and no cracks.
[0016] The second object of the present invention is achieved by adopting the following technical solution: An aluminum product is produced by the above-mentioned laser powder bed fusion additive manufacturing method for grain refinement of pure aluminum.
[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The method of the present invention adds commercial titanium oxide particle powder to pure aluminum powder, uses a mechanical mixing method to make it evenly distributed, and uses a laser additive manufacturing printing device to perform laser powder bed melting to form parts with significantly refined grains. By mixing in commercial titanium oxide particle powder, pure aluminum can achieve grain refinement and withstand more thermal stress during the printing process. During the rapid cooling process of printing, both titanium oxide and pure aluminum are melted and undergo redox reactions. Titanium remains in the aluminum matrix in the form of solute atoms and hinders the growth of grains during the solidification process, thereby directly refining the structure of pure aluminum in the absence of other heterogeneous nucleation particles.
[0018] 2. The method of the present invention is easy to operate and provides a new idea for achieving high-performance aluminum alloy grain refinement.
[0019] 3. The preparation process of the solution disclosed in the present invention is simple, and the mixed powder used does not need to be ball-milled, but can be directly mixed mechanically or ultrasonically, and is effective for pure aluminum.
[0020] 4. The proposed solution has a fast laser scanning rate and high production efficiency. It can directly affect the growth of grains by the influence of solutes alone in the absence of heterogeneous nucleation particles, thereby achieving grain refinement. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1An electron backscattered diffraction pattern of a pure aluminum structure containing 0.5% by mass of nano-titanium trioxide powder prepared by additive manufacturing in Example 1; Figure 2 This is an electron backscattered diffraction pattern of the pure aluminum structure prepared by additive manufacturing in Comparative Example 1; Figure 3 Electron backscattered diffraction pattern of pure aluminum structure containing 1% by mass of nano-titanium trioxide powder prepared by additive manufacturing in Example 2; Figure 4 The electron backscattered diffraction pattern of the pure aluminum structure containing 2% by mass of nano-titanium trioxide powder prepared by additive manufacturing in Example 3; Figure 5 This is the electron backscattered diffraction pattern of the pure aluminum structure prepared by additive manufacturing in Comparative Example 2. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below through specific implementation methods, but this should not be understood as limiting the scope of the present invention to the following examples. Without departing from the above-mentioned thought method of the present invention, various experiences or changes made according to common technical knowledge and customary means in the field should be included in the scope of the present invention.
[0023] Example 1 An aluminum product comprising the following steps: (1) Commercial pure aluminum powder and commercial nano-titanium trioxide powder in a mass ratio of 99.5:0.5 are rapidly flipped, inverted, and shaken in a three-dimensional oscillating powder mixer at a frequency of not less than 20 Hz for 2 hours to mix them uniformly to obtain a mixed powder, wherein the particle size of the commercial pure aluminum powder is 15-53 μm, and the particle size of the commercial nano-titanium trioxide powder is 100-900 nm; (2) The dried mixed powder is placed in a laser additive manufacturing printing device and formed at a laser power of 330 W, a scanning rate of 1400 mm / s, a scanning interval of 0.1 mm, and an interlayer thickness of 0.3 mm to obtain pure aluminum with refined grains.
[0024] After testing, the pure aluminum grains are mainly slender columnar crystals and a small amount of fine crystals. The statistical results show that the average grain size of the printed pure aluminum is about 135μm. Figure 1 Electron backscatter diffraction pattern of modified pure aluminum is shown.
[0025] Comparative Example 1 An aluminum product comprising the following steps: The dried commercial pure aluminum powder is placed in a laser additive manufacturing printing device and formed at a laser power of 330W, a scanning rate of 1400mm / s, a scanning spacing of 0.1mm, and an interlayer thickness of 0.3mm to obtain a pure aluminum structure, wherein the particle size of the commercial pure aluminum powder is 15~53µm.
[0026] After testing, the pure aluminum grains are mainly coarse columnar crystals and a very small amount of fine crystals. The statistical results show that the average grain size of the printed pure aluminum is about 230μm. Figure 2 Electron backscatter diffraction pattern of pure aluminum is shown.
[0027] Example 2 An aluminum product comprising the following steps: (1) placing commercial pure aluminum powder and commercial nano-titanium trioxide powder in a mass ratio of 99:1 in a three-dimensional oscillating powder mixer, rapidly flipping, inverting, and shaking for 2 hours at a frequency of not less than 20 Hz to mix them evenly to obtain a mixed powder, wherein the particle size of the commercial pure aluminum powder is 15-53 µm, and the particle size of the commercial nano-titanium trioxide powder is 100-900 nm; (2) The dried mixed powder is placed in a laser additive manufacturing printing device and formed at a laser power of 325 W, a scanning rate of 1350 mm / s, a scanning interval of 0.1 mm, and an interlayer thickness of 0.3 mm to obtain pure aluminum with refined grains.
[0028] After testing, the pure aluminum grains are mainly slender columnar crystals inside the molten pool and fine equiaxed crystals at the edge of the molten pool. The statistical results show that the average grain size of the printed pure aluminum is about 10μm, and the printed molten pool is clearly visible, such as Figure 3 Electron backscatter diffraction pattern of modified pure aluminum is shown.
[0029] Example 3 An aluminum product comprising the following steps: (1) placing commercial pure aluminum powder and commercial nano-titanium trioxide powder in a mass ratio of 98:2 in a three-dimensional rocking powder mixer, rapidly flipping, inverting, and shaking for 2 hours at a frequency of not less than 20 Hz to mix them evenly to obtain a mixed powder, wherein the particle size of the commercial pure aluminum powder is 15-53 μm, and the particle size of the commercial nano-titanium trioxide powder is 20-80 nm; (2) The dried mixed powder is placed in a laser additive manufacturing printing device and formed at a laser power of 325 W, a scanning rate of 1350 mm / s, a scanning interval of 0.1 mm, and an interlayer thickness of 0.3 mm to obtain pure aluminum with refined grains.
[0030] After testing, the pure aluminum grains are mainly small columnar crystals inside the molten pool and fine equiaxed crystals at the edge of the molten pool. The statistical results show that the average grain size of the printed pure aluminum is about 7μm, and the printed molten pool is clearly visible, such as Figure 4 Electron backscatter diffraction pattern of modified pure aluminum is shown.
[0031] Comparative Example 2 An aluminum product comprising the following steps: The dried commercial pure aluminum powder is placed in a laser additive manufacturing printing device and formed at a laser power of 325W, a scanning rate of 1350mm / s, a scanning spacing of 0.1mm, and an interlayer thickness of 0.3mm to obtain a pure aluminum structure, wherein the particle size of the commercial pure aluminum powder is 15~53µm.
[0032] After testing, the pure aluminum grains are mainly coarse columnar crystals. The statistical results show that the average grain size of the printed pure aluminum is about 270μm. Figure 5 Electron backscatter diffraction pattern of pure aluminum is shown.
[0033] Example 4 An aluminum product comprising the following steps: (1) Commercial pure aluminum powder and commercial nano-titanium trioxide powder in a mass ratio of 98.5:1.5 are rapidly flipped, inverted, and shaken in a three-dimensional oscillating powder mixer at a frequency of not less than 20 Hz for 3 hours to mix them uniformly to obtain a mixed powder, wherein the particle size of the commercial pure aluminum powder is 15-53 μm, and the particle size of the commercial nano-titanium trioxide powder is 20-80 nm; (2) The dried mixed powder is placed in a laser additive manufacturing printing device and formed at a laser power of 360 W, a scanning rate of 1500 mm / s, a scanning interval of 0.1 mm, and an interlayer thickness of 0.3 mm to obtain pure aluminum with refined grains.
[0034] After testing, it was found that pure aluminum grains are mainly slender columnar crystals, and statistical results show that the average grain size of printed pure aluminum is about 8μm.
[0035] Comparative Example 3 (1) Mixing commercial pure aluminum powder and commercial nano-titanium trioxide powder in a mass ratio of 98.5:1.5 for 10 minutes to obtain a mixed powder, wherein the particle size of the commercial pure aluminum powder is 15-53 μm, and the particle size of the commercial nano-titanium trioxide powder is 20-80 nm; (2) The dried mixed powder is placed in a laser additive manufacturing printing device and formed at a laser power of 180 W, a scanning rate of 1500 mm / s, a scanning interval of 0.2 mm, and an interlayer thickness of 0.3 mm to obtain pure aluminum with refined grains.
[0036] After testing, it was found that the pure aluminum grains were mainly coarse columnar crystals and a very small amount of fine crystals. Statistical results showed that the average grain size of the printed pure aluminum was about 320μm.
[0037] Example 5 An aluminum product comprising the following steps: (1) Commercial pure aluminum powder and commercial nano-titanium trioxide powder with a mass ratio of 99:1 are rapidly flipped, inverted, and shaken in a three-dimensional oscillating powder mixer at a frequency of not less than 20 Hz for 3 hours to mix them uniformly to obtain a mixed powder, wherein the particle size of the commercial pure aluminum powder is 15-53 µm, and the particle size of the commercial nano-titanium trioxide powder is 900-1000 nm; (2) The dried mixed powder is placed in a laser additive manufacturing printing device and formed at a laser power of 330 W, a scanning rate of 1400 mm / s, a scanning interval of 0.1 mm, and an interlayer thickness of 0.3 mm to obtain pure aluminum with refined grains.
[0038] After testing, it was found that the pure aluminum grains were mainly slender columnar crystals and a small amount of fine crystals. Statistical results showed that the average grain size of the printed pure aluminum was about 15μm.
[0039] Example 6 An aluminum product comprising the following steps: (1) placing commercial pure aluminum powder and commercial nano-titanium trioxide powder in a mass ratio of 99:1 in a three-dimensional oscillating powder mixer, rapidly flipping, inverting, and shaking for 3 hours at a frequency of not less than 20 Hz to mix them evenly to obtain a mixed powder, wherein the particle size of the commercial pure aluminum powder is 15-53 µm, and the particle size of the commercial nano-titanium trioxide powder is 1-10 nm; (2) The dried mixed powder is placed in a laser additive manufacturing printing device and formed at a laser power of 330 W, a scanning rate of 1400 mm / s, a scanning interval of 0.1 mm, and an interlayer thickness of 0.3 mm to obtain pure aluminum with refined grains.
[0040] After testing, it was found that the pure aluminum grains were mainly slender columnar crystals and a small amount of fine crystals. Statistical results showed that the average grain size of the printed pure aluminum was about 9μm.
[0041] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing, characterized in that: The steps include: S1: uniformly mix pure aluminum powder and titanium oxide powder in a mass ratio of (98-99.5):(0.5-2) to obtain a mixed powder; S2: The mixed powder is placed in a laser powder bed fusion additive manufacturing forming device, and grain refinement is performed on it with a laser power of 200~400W, a scanning rate of 200~2000mm / s, a scanning spacing of 0.08~0.12mm, and an interlayer thickness of 0.3mm.
2. The method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing according to claim 1, characterized in that: In step S1, a pre-processing step is also included: The pure aluminum powder was placed in a vacuum drying oven for drying.
3. The method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing according to claim 1, characterized in that: In step S1, the particle size of the pure aluminum powder is 15-53 μm.
4. The method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing according to claim 2, characterized in that: The particle size of the nano titanium oxide powder is 0.00006-0.2 of the particle size of the pure aluminum powder.
5. The method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing according to claim 4, characterized in that: The particle size of the nano titanium oxide powder is 1-1000nm.
6. The method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing according to claim 5, characterized in that: The particle size of the nano titanium oxide powder is 20-900 nm.
7. The method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing according to claim 6, characterized in that: The particle size of the nano titanium oxide powder is 20-80 nm.
8. The method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing according to claim 1, characterized in that: In step S1, the specific method of uniformly mixing the powders is as follows: Put pure aluminum powder and titanium oxide powder in a mass ratio of (98~99.5):(0.5~2) into a three-dimensional swinging mechanical powder mixer, and quickly flip, invert and shake for 2~3 hours at a frequency of not less than 20Hz to mix them evenly.
9. The method for grain refinement of pure aluminum by laser powder bed fusion additive manufacturing according to claim 1, characterized in that: In step S2, the laser power is 300-380 W, the scanning rate is 1000-1800 mm / s, and the scanning interval is 0.1 mm.
Citation Information
Patent Citations
Al-TiO2-C grain refiner, preparation method thereof and commercial-purity aluminum refining method
CN105002389A
Aluminum alloys with grain refiners, and methods for making and using same
CN110546287A
Preparation method for aluminum alloy based on pulsed electric field synchronous auxiliary laser 3D printing
CN116604033A
Aluminum alloys with grain refiners, and methods of making and using same
CN117144196A
Preparation method of additive manufacturing in-situ TiC ceramic particle reinforced aluminum-based composite material
CN117753988A